THE ROLE OF FIRE IN THE TRADITIONAL RITUAL CULTURE OF DAGESTAN PEOPLES - Musaeva, Majsarat Kamilovna (History, Archeology and Ethnography of the Caucasus, 2024)
Fire is regarded as one of the earliest “ambivalent essences”, tamed by humans, and an integral part of the ritual culture of the peoples of Dagestan. The versatility of such a symbol – which has given rise to numerous ideas, beliefs, and attributes of holidays, rites, and rituals – is not fully explored or presented in the works of Dagestani and other Russian researchers. Rather than considering the utilitarian aspect of fire, this paper examines fire as a symbol encompassing many facets of the traditional ideas of people. It portrays fire as a microcosm that influences individuals and the environment, serving as a tool of knowledge with significant epistemological potential. Fire, as a sacred symbol, is deeply rooted in history, culture, and ethnographic traditions among nearly all peoples of the world. In this regard, it is of particular interest for studying the history of religious ideas, festive cultures, and the mental preferences of the peoples of Dagestan. A systematic study of the genesis of the symbolism of “fire” and its derivatives (such as ash, coal, and firebrands), examined as part of a comprehensive system, allows us to illustrate their material roots, historical bases, and their constant connection with reality. This approach reveals the dual perception of fire and provides an analysis of its super-symbols, solar signs, and the cult of the sun and fire within the belief systems of the peoples of Dagestan. The methodological foundation of this study encompasses the works of Russian and foreign scholars: historians, ethnographers, and folklorists, as well as the author’s own field research and observations. It employs comparative-historical and retrospective methods with a cultural approach to ethnocultural mutual influences. The findings suggest that tamed fire in the hearth, with its harnessed energy, indelibly marked the spiritual culture and ideas of humanity, securing a significant role in the rituals of both familial and public life among the peoples of Dagestan.